(untitled) (Acta Scientiarum. Health Sciences, 2016)
Current retrospective, descriptive, document-based study identified the risk factors in the administration of antimicrobial drugs by the nursing team. The hospital records at the Hematology and Oncology clinics of patients treated with antimicrobial agents in a hospital in the center-western region of the state of Minas Gerais, Brazil, between January 2008 and December 2011, were analyzed. Data were investigated with IBM program, Statistical Package of Social Sciences (SPSS) 21.0 and inferential statistics. Chi-square and Fisher´s exact tests were employed to assess the differences between the categorical variables. Risk factors related to the administration of antimicrobial agents by the nursing team comprised lack of records of phlogistic infection signs; inadequate schedules for the administration of antimicrobial drugs; lack of precaution and isolation measures and of swab sampling. Continuous education programs for nurses, focusing on safe administration of antimicrobial agents, are highly relevant.